2021
DOI: 10.1039/d1cy00268f
|View full text |Cite
|
Sign up to set email alerts
|

Self-sufficient asymmetric reduction of β-ketoesters catalysed by a novel and robust thermophilic alcohol dehydrogenase co-immobilised with NADH

Abstract: A highly robust and productive self-sufficient heterogeneous biocatalysts to asymmetrically reduce β-ketoesters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 64 publications
1
44
0
Order By: Relevance
“…[119][120][121][122][123][124][125] For instance, it has been demonstrated that the possibility of co-immobilizing enzymes and cofactors enables not only the re-use of enzymes, but also the regeneration and continuous reuse of expensive cofactors. [126][127][128][129][130] Many enzymes can be found (or else tuned) to operate under relatively similar reaction conditions (pH, temperature, and pressure) meaning that the linking together of enzymes in this way is much easier than with conventional metal-based catalysts. Indeed, some spectacular industrial examples in the pharmaceutical industry exemplify the power of this approach.…”
Section: Roberto Fernandez-lafuentementioning
confidence: 99%
“…[119][120][121][122][123][124][125] For instance, it has been demonstrated that the possibility of co-immobilizing enzymes and cofactors enables not only the re-use of enzymes, but also the regeneration and continuous reuse of expensive cofactors. [126][127][128][129][130] Many enzymes can be found (or else tuned) to operate under relatively similar reaction conditions (pH, temperature, and pressure) meaning that the linking together of enzymes in this way is much easier than with conventional metal-based catalysts. Indeed, some spectacular industrial examples in the pharmaceutical industry exemplify the power of this approach.…”
Section: Roberto Fernandez-lafuentementioning
confidence: 99%
“…Wildtype TtHBDH and its His-tagged variant (TtHBDH-His) were expressed and purified, as described elsewhere. 27 Briefly, pET28b plasmids encoding the corresponding enzymes (Figure S12) were transformed in BL21 (DE3) E. coli cells. Colonies were picked and grown in LB-containing kanamycin (30 μg mL −1 ).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Beyond the glucose oxidase/peroxidase system exhaustively used in material engineering for glucose detection, we select the NADH-dependent and His-tagged 3-hydroxybutyryl-CoA dehydrogenase from Thermus thermophilus HB27 (TtHBDH-His) and a formate dehydrogenase from Candida boidinii (His-CbFDH) as a bienzyme model system (Figure ). , We found that these two His-tagged enzymes were selectively immobilized on naked YSZ membranes without requiring the surface activation with NiO nanoparticles. Finally, we studied the effect of flow rate and cofactor concentration on the overall specific productivity of the coimmobilized multienzyme system for the continuous asymmetric reduction of β-ketoesters with in situ NADH recycling …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…López-Gallego and coworkers reported a self-sufficient heterogeneous biocatalyst by coimmobilising both enzyme and cofactor on glyoxyl-agarose macroporous beads (Orrego et al, 2021). After covalent immobilisation of a thermophilic (S)-2hydroxybutyryl-CoA dehydrogenase from Thermus thermophilus HB27 (Tt27-HBDH), the remaining formyl groups on the carrier allowed for a subsequent coating with polyethyleneimine (PEI) to give a cationic layer in which NADH molecules could be embedded and reversibly immobilised through ionic interactions.…”
Section: Adh Immobilisationmentioning
confidence: 99%